An evaluation of serum paraoxonase together with arylesterase activities and oxidative stress in children with intractable epilepsy: a cross-sectional study. - Calik, M; Sarikaya, S; Oguz , E; Kocaturk, O; Koca, B; Gungor , HE; Aksoy, N; Yoldas, TK; Iscan, AKIN; İŞCAN, AKIN (My University, 2014)
Epilepsy is the most common chronic neurological illness in childhood and adolescence. The aim of this study was to investigate paraoxonase and arylesterase activities along with oxidative status parameters in children with intractable epilepsy. The study comprised 42 subjects with intractable epilepsy and a control group of 35 healthy subjects. Serum paraoxonase and arylesterase activities, and lipid hydroperoxide levels were determined. All paraoxonase and arylesterase activities were significantly lower in the intractable epilepsy subjects than in the controls (P < 0.001), whereas lipid hydroperoxide levels were significantly higher (P < 0.05).